Hubungan Peran Tenaga Kefarmasian dan Dukungan Keluarga dengan Tingkat Kepatuhan Minum Obat Antihipertensi di Apotek “X” Kota Denpasar - Ni Putu Wintariani; Dewi Puspita Apsari; Ni Putu Aryanti Suryaningsih; I Putu Tangkas Suwantara; Fitria Megawati (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Hypertension is a condition where a person's blood pressure is above normal, which is 140 mmHg systolic or 90 mmHg diastolic. Hypertension causes increased morbidity, with almost the same prevalence in developing and developed countries. In terms of medication adherence, patient awareness of treatment plays an important role. The role of family members in adherence to taking hypertension medication is very important. Support and attention from the family is one of the supporting factors, the success of hypertension treatment, so it is expected to reduce the mortality rate. Clinical pharmacy services in pharmacies are part of pharmaceutical services that are directly responsible for patients involved in dispensing. In this study, researchers tried to understand the relationship between the role of family support and the role of pharmacists in taking high blood pressure drugs at the